The impact of university students' commitment on in- and extra-role performance. (8th April 2014) - Felfe, Jörg; Schyns, Birgit; Tymon, Alex
Abstract : Purpose: – Research has shown that employee commitment is an important factor in performance. Research into student commitment in the university context is less common and only few studies explore the different components and foci of commitment. The purpose of this paper is to examine the meaning of students' commitment in the university context. Design/methodology/approach: – Based on a survey of 530 students, the results confirmed that, similar to the work context, different components and foci of commitment exist. Findings: – Commitment to the university is primarily positively related to extra-role performance. Commitment to the study subject is positively related to both in-role and extra-role performance. Affective commitment to the university shows the strongest relationship with extra-role performance. However, there is a potential conflict between the two types of performance. The relationship between affective commitment to the university and extra-role performance decreases for students with a high intention to study efficiently as an indicator of in-role performance. Practical implications: – The paper concludes that universities should strive to improve their students' commitment, especially affective commitment to encourage a balance of both in-role and extra-role performance. Originality/value: – This study looks into different foci and components of commitment and the potential for conflict for students between in-role and extra-role performance. The study has shown that commitment to the university and to the study subject likely enhances students' in-role and extra-role performance; both of which are important to numerous stakeholders in the education context. As in other contexts, affective commitment has been shown to be the most powerful predictor of performance. This knowledge can help universities target their resources when trying to foster student commitment. However, because students might feel that extra-role performance is in conflict with in-role performance, universities might want to emphasize the benefits of both types of performance.